Triphasic calcium‐based implant material resorbs and is replaced with bone in ovariectomized rats with or without bisphosphonate treatment. Issue 10 (25th January 2022) - Shaul, Jonathan; Hill, Ronald; Bruder, Scott; Tilton, Annemarie; Howe, James
Abstract: This study evaluated the effects of AGN1, a triphasic calcium‐based material, and alendronate (A) on distal femoral defect bone repair in ovariectomized (OVX) rats. Of 106 rats, 92 were OVX'ed at 12 weeks old and underwent a 12‐week induction period. Animals were randomized into five groups: OVX Control, OVX Alendronate Control, Normal Control, OVX Implantation, OVX Alendronate + Implantation. OVX Alendronate Control and OVX Alendronate + Implantation groups received alendronate injection twice weekly (0.015 mg/kg) from 6 weeks until sacrifice. Twelve weeks after OVX, 2.5 mm diameter by 4.0 mm long cylindrical, bilateral distal femoral defects were created in experimental animals. One defect was left empty, and one filled with AGN1. Dual‐energy X‐ray absorptiometry, microcomputed tomography, and histomorphometry were performed 0‐, 6‐, 12‐, and 18‐week postdefect/implantation surgery ( N = 6–8/group). Results showed OVX induced significant and progressive bone loss which alendronate prevented. Histomorphometry demonstrated rapid AGN1 resorption: AGN1 resorbed from 95.1 ± 0.7% filling of the implant site (week 0) to 1.3 ± 1.0% (18 weeks) with no significant alendronate effect (1.6 ± 1.1%, 18 weeks). Bone formation in empty defects consisted primarily of cortical wall healing, whereas AGN1 implants demonstrated cortical wall healing with new trabecular bone filling the subcortical space. Alendronate dramatically increased bone formation in empty and AGN1 defects. We conclude AGN1 is resorbed and replaced by new cortical and trabecular bone in this OVX model, and alendronate did not compromise these effects.